A Novel R2R3-MYB Transcription Factor BpMYB106 of Birch (Betula platyphylla) Confers Increased Photosynthesis and Growth Rate through Up-regulating Photosynthetic Gene Expression - Zhou, Chenguang; Li, Chenghao (Frontiers in Plant Science, 2016)
We isolated a R2R3-MYB transcription factor BpMYB106, which regulates photosynthesis in birch (Betula platyphylla Suk.). BpMYB106 mainly expresses in the leaf and shoot tip of birch, and its protein is localized in the nucleus. We further fused isolated a 1588 bp promoter of BpMYB106 and analyzed it by PLACE, which showed some cis-acting elements related to photosynthesis. BpMYB106 promoter β-glucuronidase (GUS) reporter fusion studies gene, the result, showed the GUS reporter gene in transgenic birch with BpMYB106 promoter showed strong activities in shoot tip, cotyledon margins, and mature leaf trichomes. The overexpression of BpMYB106 in birch resulted in significantly increased trichome density, net photosynthetic rate, and growth rate as compared with the wild-type birch. RNA-Seq profiling revealed the upregulation of several photosynthesis-related genes in the photosynthesis and oxidative phosphorylation pathways in the leaves of transgenic plants. Yeast one-hybrid analysis, coupled with transient assay in tobacco, revealed that BpMYB106 binds a MYB binding site MYB2 in differentially expressed gene promoters. Thus, BpMYB106 may directly activate the expression of a range of photosynthesis related genes through interacting with the MYB2 element in their promoters. Our study demonstrating the overexpression of BpMYB106 – a R2R3-MYB transcription factor – upregulates the genes of the photosynthesis and oxidative phosphorylation pathways to improve photosynthesis.